Factors Influencing Purchase Intention in Digital Marketing: A Thematic Analysis - Rana, Md. Sohel; Sharmin, Shadia; SM Nahidul Islam (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study explores the elements influencing Bangladeshi consumers' purchase intentions in the digital marketing sector, a topic rarely addressed in previous research. Guided via a qualitative approach, semi-structured interviews were performed, and thematic analysis was carried out. Key themes identified include convenience and time-saving, access to detailed information and customer reviews, price sensitivity and comparison, social Influence, technological integration, visual appeal and content quality, and customer service experience. The findings provide valuable insights for marketers to better apprehend patron behavior and help policymakers perceive vital factors for powerful product techniques inside the digital marketplace. Theoretical implications include a deeper know-how of consumer decision-making in a virtual context, especially in rising markets like Bangladesh.